Blessings - Quindlen, Anna. (New York : arrow books, 2002)
Skip Cuddy, caretaker of the Blessing estate, finds a baby asleep in a box and decides he wants to keep her. The secrets of the past, how they affect the decisions and lives of people in the present are at the center of this work.
All Ages.
43
Keywords: Foundlings -- Fiction; Administration of estates -- Fiction; Women landowners -- Fiction